Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.icarus.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial locations of water on Mars: Improved resolution maps based on Mars Odyssey Neutron Spectrometer data

Abstract: We present a map of the near subsurface hydrogen distribution on Mars, based on epithermal neutron data from the Mars Odyssey Neutron Spectrometer. The map's spatial resolution is approximately improved two-fold via a new form of the pixon image reconstruction technique. We discover hydrogen-rich mineralogy far from the poles, including ∼10 wt. % water equivalent hydrogen (WEH) on the flanks of the Tharsis Montes and >40 wt. % WEH at the Medusae Fossae Formation (MFF). The high WEH abundance at the MFF implies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 56 publications
6
76
1
Order By: Relevance
“…• The change in prevalence of active bedforms to those that are inactive as well as the shift in dune morphology toward characteristics consistent with stability and increasing nonaeolian modification (SI ≥ 2) both occur at~60°S and coincide with the edge of high concentrations of H 2 O-equivalent hydrogen content observed by the Neutron Spectrometer (Feldman et al, 2004;Wilson et al, 2018). Generally speaking, conditions where these dune fields formed, such as ample sediment supply and winds at or above saltation strength, remain favorable for aeolian activity today.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…• The change in prevalence of active bedforms to those that are inactive as well as the shift in dune morphology toward characteristics consistent with stability and increasing nonaeolian modification (SI ≥ 2) both occur at~60°S and coincide with the edge of high concentrations of H 2 O-equivalent hydrogen content observed by the Neutron Spectrometer (Feldman et al, 2004;Wilson et al, 2018). Generally speaking, conditions where these dune fields formed, such as ample sediment supply and winds at or above saltation strength, remain favorable for aeolian activity today.…”
Section: Discussionmentioning
confidence: 96%
“…Fenton and Hayward (2010) interpreted these morphological characteristics as evidence of progressive erosion by nonaeolian processes and progressive stabilization of the dune fields. Fenton and Hayward (2010) observed that the shift in dune morphology poleward of~60°S latitude (where SI = 2 dune fields first appear) corresponded with concentrations >~20% of near-surface water equivalent hydrogen in Mars Odyssey Neutron Spectrometer maps; these concentrations are interpreted to be ground ice (Feldman et al, 2004;Wilson et al, 2018). Fenton and Hayward (2010) observed that the shift in dune morphology poleward of~60°S latitude (where SI = 2 dune fields first appear) corresponded with concentrations >~20% of near-surface water equivalent hydrogen in Mars Odyssey Neutron Spectrometer maps; these concentrations are interpreted to be ground ice (Feldman et al, 2004;Wilson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements of hydrogen abundance in the upper tens of centimeters of the Martian regolith show that the middle to high latitudes of present‐day Mars contain significant quantities of water‐equivalent hydrogen, inferred to be subsurface ice in both hemispheres (Boynton et al, ; Feldman et al, ; Wilson et al, ). This ice content has been confirmed by many morphological observations, including ice revealed by small impacts (Byrne et al, ), thermal contraction cracks (e.g., Levy et al, ; Mangold, ; Ulrich et al, ), lobate/rampart impact ejectas (e.g., Squyres & Carr, ), pedestal craters (e.g., Costard, ), sublimation pits (e.g., Costard & Kargel, ; Morgenstern et al, ; Séjourné et al, ; Soare et al, ), clastic networks and lobes (e.g., Gallagher & Balme, ), and—perhaps most reliably—remote (e.g., Dundas et al, ) and in situ (e.g., Mellon et al, ) observations of massive ice.…”
Section: Introductionmentioning
confidence: 99%
“…The most probable reconstruction is then found by varying the number of pixons to maximize the posterior probability (equation ). Alternatively, the locally adaptive pixon (LAP) method uses the definition of a local misfit statistic, ER , to determine how the pixon sizes must be modified at each location (Wilson et al, ).…”
Section: Image Reconstruction In Planetary Sciencesmentioning
confidence: 99%
“…The pixon method (Pina & Puetter, ) has successfully been used in a range of disciplines including medical imaging and infrared and X‐ray astronomy (Puetter, , and references therein). In addition, it has recently been used to reconstruct remotely sensed neutron (Eke et al, ; Wilson et al, ) and gamma ray data (Lawrence et al, ; Wilson et al, ) and has been shown to give a spatial resolution 1.5–2 times that of other methods in reconstructing planetary data sets (Lawrence et al, ). A modified pixon technique in which the reconstructed image is the result of combining decoupled regions has been developed for use when sharp boundaries are expected to exist based on other data (Eke et al, ; Wilson et al, ).…”
Section: Image Reconstruction In Planetary Sciencesmentioning
confidence: 99%